¿Cómo enverdecer el derecho comunitario andino?: propuestas para insertar políticas de precios al carbono en un contexto de recuperación verde de la Comunidad Andina - Peña Alegría, Pablo Guillermo (2021)
The global pandemic crisis has created a valuable opportunity to promote green recovery policies at the level of regional integration blocks that are tightly aligned to climate policies, including carbon pricing. The European Union’s Green Deal is an example. We propose that the Andean Community (CAN, by its acronym in Spanish) follows that example by establishing carbon pricing policies in its community law framework, adapting it to its level of regional integration and to the needs of its member countries. We suggest five ideas of carbon pricing policies that Andean countries could adopt within the CAN: phasing out of fossil fuel subsidies, regulating a border-adjustment carbon tax, creating a regional carbon tax, defining a reference social carbon price, and establishing a regional carbon market. To achieve them, the Andean Community can choose between establishing community legislation of uniformization or harmonization. We argue that harmonization is the best option because it would allow for setting a realistic and viable goal, freeing each member country to decide how to attain it.